Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) pada Pembelajaran Pendidikan Agama Islam - Irfan Taufik (Institut Agama Islam Negeri Palopo, 2019)
This research discusses the application of the Contextual Teaching and Learning (CTL) learning model in improving student learning outcomes, the purpose of the research in this paper is how to use the Contextual Learning learning model and Learning (CTL) can improve student learning outcomes. The type of research used in this study is classroom action research (CAR). The research subjects were students of class XI Administration 3 Vocational High School (SMK) Negeri 1 Palopo 2018/2019 academic year consisting of 7 male students and 18 female students. The data in this study were obtained from the results of observations of student activities (observation sheets) and final cycle test instruments. Furthermore, the data of this study were analyzed with qualitative descriptive. The learning model of Contextual Teaching and Learning (CTL) in the subjects can improve student learning outcomes. This can be seen from students who enthusiastically receive learning material and students are not ashamed to practice the material directly received, the results showed that during the final test Cycle I student learning outcomes amounted to 73.52%, then in cycle II Discover the results of learning student learning material at 81.48% or around 7.91% in the realm of cognitive, affective, and psychomotor aspects.